2023
DOI: 10.3390/ijms241311069
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Expression of Renal Proximal Tubular Epithelial Cells and Their Extracellular Vesicles in an Inflammatory Microenvironment In Vitro

Patrick C. Baer,
Ann-Kathrin Neuhoff,
Ralf Schubert

Abstract: Renal proximal tubular epithelial cells (PTCs) are central players during renal inflammation. In response to inflammatory signals, PTCs not only self-express altered mRNAs, microRNAs (miRNAs), proteins, and lipids, but also release altered extracellular vesicles (EVs). These EVs also carry inflammation-specific cargo molecules and are key players in cell–cell-communication. Understanding the precise molecular and cellular mechanisms that lead to inflammation in the kidney is the most important way to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…We observed that Akt1 mRNA levels are downregulated following TLR4 or TLR2 stimulation [94]. This is in line with the description of Akt1 as a target gene of the miRNA miR-155-5p [66,97], whose expression has been consistently reported to be upregulated by various members of the TLR family [4,5,7,11,12,20,24,25,34,42,47,58,[70][71][72][73]83,[90][91][92][98][99][100][101][102][103]. In addition, Akt1 activity is subject to post-transcriptional modulation.…”
Section: Macrophage Polarization Influenced By Mirnassupporting
confidence: 89%
See 3 more Smart Citations
“…We observed that Akt1 mRNA levels are downregulated following TLR4 or TLR2 stimulation [94]. This is in line with the description of Akt1 as a target gene of the miRNA miR-155-5p [66,97], whose expression has been consistently reported to be upregulated by various members of the TLR family [4,5,7,11,12,20,24,25,34,42,47,58,[70][71][72][73]83,[90][91][92][98][99][100][101][102][103]. In addition, Akt1 activity is subject to post-transcriptional modulation.…”
Section: Macrophage Polarization Influenced By Mirnassupporting
confidence: 89%
“…Changes in the expression levels of the so-called early miRNAs occur immediately after ligand binding. For example, miR-155-5p was reported to be upregulated within 2 h of stimulation [57,72,[91][92][93]. As a higher-ranking miRNA, miR-155-5p then regulates the expression of further miRNAs of the late response [57,74,89].…”
Section: Tlr Signaling Cascade and Mirna Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marhuenda and coworkers show that culturing primary alveolar epithelial cells on lung extracellular matrix-derived hydrogels facilitated the prolonged culturing of these cells and enhanced the preservation of the type II phenotype [7]. Baer and coworkers characterised the mRNA expression of renal proximal tubular epithelial cells and the cargo in extracellular vesicles in an inflammatory microenvironment [8]. This study demonstrates the altered miRNA expression of epithelial cells and their released vesicles during induced inflammation, with only three miRNAs overlapping between cells and vesicles.…”
mentioning
confidence: 91%